Cigarette Smoking & Electronic Cigarette Use among Malaysian Adolescents: Urgent Call for Action - Prof Dr Mohamad Haniki Nik Mohamed (IIUM Press, International Islamic University Malaysia, 2024)
Adolescence is an important developmental period1,2 characterized by engagement in risky behaviours, including the use of tobacco products such as cigarettes and electronic nicotine delivery systems such as e-cigarettes (e-cigs)3. The use of tobacco in the form of cigarettes and e-cigs is indeed of interest to the public health community and the nation at large. E-cigs are defined as devices that deliver aerosolized or vaporised nicotine form heating of liquids (e-juice) with constituents including nicotine, propylene glycol, glycerol, and other flavouring agents. It has been reported that 90% of smokers start smoking before the age of 18 years4. The Tobacco & E-Cigarette Survey among Malaysian Adolescents (TECMA) 2016, a nationwide school-based survey, found 11.7% current cigarette smokers among students between 10 to 19 years old. 78.7% of ever cigarette smokers tried their first cigarette before the age of 14. In addition, 9.1% of the students were current e-cigarettes users, with 40.9% vaping once a day and 33.9% doing it 2 to 5 times per day. Alarmingly, data from the 2022 Adolescent Health Survey found a sharp increase in adolescent vaping prevalence among adolescents aged 13-17 years old, reaching a high of 14.9% in 2022.6 E-cigs are heavily promoted directly to users include advertising and promotion at combustible cigarette point-of-sale (e.g., behind cashier's counter). E-cigs are also promoted via physical and online shops, internet, social media, events, etc. According to TECMA, 10.6% of school-going adolescents aged 10-19 years were offered a free trial session of e-cigarette/vape while 7.9% were offered a free e-cigarette/ vape liquid (e-liquid)5. With proliferation of e-cig promotions via the social media, internet, and vape shops (some under the guise of selling electronic products, handphones, etc.,), using celebrities and others, the number of dual users and vapers among non-smokers, especially adolescents in Malaysia can be even higher now. In early adolescence, development of executive function and neurocognitive processes in the brain has not fully matured. Adolescence is a sensitive period for maturation of brain circuits that regulate cognition and emotion, with resulting vulnerability to the effects of nicotine and tobacco. The rapidly changing, immature adolescent brain has differing sensitivity to drugs such as nicotine and tobacco, and drug exposure during this time can lead to long-term changes in neural circuitry and behaviour6. The American Academy of Pediatrics produced a policy statement showing evidence regarding the effects of nicotine on the developing brain. Nicotine has neurotoxic effects on the developing brain, an effect on the brain as a "gateway" drug for cocaine and other illicit drugs. The gateway theory postulates that smoking, especially among adolescence, increases the risk of substance use due to effects of nicotine, shown to be a neuroteratogen that exerts long-term, maturational effects at critical stages of brain development7.